PENGARUH PUPUK NPK TERHADAP SERAPAN N DAN HASIL BEBERAPA KULTIVAR PADI PADA BUDIDAYA SRI DI VERTISOL KULON PROGO - , DYAH PRASETYANINGTYAS; , Dr. Ir. Benito Heru Purwanto, MS., M.Agr. Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Rice production from year to year is declining, while the number of people in Indonesia increase. Therefore it is necessary to use cultivation techniques of Rice Cultivation SRI (System of Rice Intensification) for increasing plant growth production.This experiment aimed to determine the uptake of nitrogen and productivity of four rice cultivars in SRI method. This experiment had been conducted in December 2012 â March 2013 in Vertisol Ngestiharjo Village, Wates District, Kulon Progo Regency, Yogyakarta. The treatments consists of four rice cultivars and organic-inorganic fertilizer. The results showed that yields of Mekongga cultivar with organic-inorganic fertilizer treatment was the highest (8.10 t/ha). The rice cultivars had different levels of nutrient uptake. Cibogo cultivar with inorganic-organic fertilizer treatment had the highest uptake levels of nitrogen (0.276 g/clump).